2015
DOI: 10.1039/c5ta03215f
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic titanium dioxide based nanomaterials: synthesis, characteristics, and photocatalytic application in pollutant degradation

Abstract: Recent advances in synthesis methods, structure and enhanced photoactivity of magnetic titanium dioxide based photocatalysts are highlighted in this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 129 publications
(165 reference statements)
0
34
0
Order By: Relevance
“…Therefore, it is necessary to bring into perspective the current developments in the tailoring and application of such materials in water treatment. A few reviews are available mainly on the synthesis, structure, and various applications of magnetic materials [83][84][85][86][87][88]. This review exclusively discusses the most recent developments in terms of the synthesis and exploitation of various magnetic nanocomposite photocatalysts in water pollution mitigation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to bring into perspective the current developments in the tailoring and application of such materials in water treatment. A few reviews are available mainly on the synthesis, structure, and various applications of magnetic materials [83][84][85][86][87][88]. This review exclusively discusses the most recent developments in terms of the synthesis and exploitation of various magnetic nanocomposite photocatalysts in water pollution mitigation.…”
Section: Introductionmentioning
confidence: 99%
“…The drastic difference in the intensity signals indicates a different amount of solvent that increased from sample A to D. Indeed, this result agree well with the surface area analysis from BET isotherms (Table 1), where the increased value of the surface to mass ratio from A to D, implies an increment of the possibility to adsorb the solvent. Samples A and B had no supplementary signals, demonstrating a complete crystallization already at 150 °C, a temperature notably lower with respect to the literature data [1,26]. On the contrary, samples C and D possessed weak exothermic peaks at 385 °C, correlated with the phase transition of the particles from amorphous to the tetragonal anatase structure.…”
Section: Resultsmentioning
confidence: 53%
“…Generally, a thick SiO 2 layer is inserted between the internal core (Fe 3 O 4 ) and the external catalyst (TiO 2 ) to prevent the Fe 3 O 4 -TiO 2 direct contact that would decrease the photodegradation activity [22,23,24,25]. Indeed, it has been demonstrated that the TiO 2 surface area decreased if supported on a magnetic substrate [26]. Consequently, our attention was focused to the possibility of using, in the titania sol-gel synthesis route, very small amounts of magnetite, exploited as germination seeds affecting the nucleation, formation, and morphology of the TiO 2 NPs.…”
Section: Introductionmentioning
confidence: 99%
“…12). Considering that the current magnetic nanoparticles preparation methods generally have low yields27282930, there is few large-scale industrial productions, resulting in high purchase costs. However, in most cases, this method needs only 6.0 mg Fe 3 O 4 NPs and 0.3 mg C 16 mimBr for 4 mL of sample solution and the total cost were less than 0.1 dollar.…”
Section: Resultsmentioning
confidence: 99%